Comparison of statistical mix-design proportions of high strength self-compacting concrete - (:unkn) unknown (My University, 2012)
High strength self-compacting concrete (HS-SCC) has increasing demand in infrastructure works where high compressive strength of up to 100 MPa is achieved with a special type of superfluid concrete mixture. SCC was developed in Japan at the end of the 1990's and the scientific rules to manufacture SCC were developed by Japanese Scientists. Concrete mixture proportions for HS-SCC have been varied widely depending on many factors and sensitive interactions between components. Statistical mixture design (SMD) methods can be used to enhance our understanding of concrete mixtures by providing cost effective fresh and hardened concrete properties. In this study, the optimization results of HS-SCC mixture proportions in C100/115 concrete class using SMD methods were compared with the scientific rules of Okamura and coworkers to manufacture SCC. As a result of this study, suggested concrete mixture proportions through SMD method were confirmed by Okamura's Rules.
Keywords: Concrete mixture proportioning; High-strength concrete; Self-compacting concrete; Statistical mixture design